(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This thesis examines the pragmalinguistic features of corporate presentations and written reports, focusing on the persuasive strategies and hedging devices professional communicators deploy in these genres. Drawing on genre theory, metadiscourse analysis, and corpus-based pragmalinguistics, the study identifies how corporate communicators manage epistemic commitment, organize complex information, and position themselves persuasively in relation to their audiences. The analysis demonstrates that hedging performs not only epistemic but also interpersonal and institutional functions, and that the appropriate management of hedging and boosting constitutes a central dimension of professional communicative competence in international business contexts.